Ceramic particle reinforced wear-resistant steel ball and preparation method thereof
By adding iron-based materials to the outer layer of ceramic particles and combining them with the steel ball matrix, the problem of high brittleness in the preparation of ceramic particles is solved, and ceramic particle-strengthening wear-resistant steel with high hardness, excellent wear resistance and impact resistance is achieved. Balls, suitable for large mills, reduce wear rates and improve economic and social benefits.
Patent Information
- Application Number
- CN202411217496.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
AI Technical Summary
Wear-resistant wear balls prepared by ceramic particles are highly brittle in large mills, prone to cracking and peeling, and their excellent wear resistance cannot be exerted.
Add an iron-based material to the outer layer of wear-resistant ceramic particles, and add wear-resistant ceramic particles containing iron-based materials to the wear-resistant steel ball to achieve a firm metallurgical combination with the steel ball matrix. After forging and heat treatment, it can be used. Form ceramic particle-reinforced wear-resistant steel balls with high hardness, excellent wear resistance and impact resistance.
The obtained ceramic particle-reinforced wear-resistant steel ball has high hardness, excellent wear resistance and impact resistance. The surface hardness exceeds 65HRC, the core hardness exceeds 63HRC, and the impact toughness exceeds 22J/cm2. It can continuously fall by 2500 in a large mill. The wear rate is reduced by more than 45% compared with the forged 65Mn grinding ball.
Smart Images

Figure BDA0005021975600000151
Abstract
Description
Technical Field
[0001] The invention discloses a wear-resistant steel ball and a preparation method thereof, in particular to a ceramic particle reinforced wear-resistant steel ball and a preparation method thereof, belonging to the technical field of wear-resistant materials. Background Art
[0002] Grinding ball is a kind of grinding medium used in ball mill, which is widely used in building materials, mineral processing, electric power, chemical industry and other industries, with an annual consumption of more than 10 million tons. At present, the wear-resistant materials used for grinding balls in China mainly include carbide-containing ductile iron, low-alloy white cast iron and high-chromium white cast iron. The production cost of carbide-containing ductile iron is low, but its performance is unstable and the breakage rate is high; low-alloy white cast iron has low toughness; high-chromium white cast iron has better performance, but the production cost is high, and it is difficult to promote it in large quantities. In addition, high-chromium cast iron has little wear resistance under wet grinding conditions of corrosive media, and its toughness is also insufficient. The more common grinding ball varieties in the foreign market include chromium alloy cast balls, medium and high carbon forged steel balls, bainite forged steel balls, bainite ductile iron grinding balls, bainite / martensite multiphase ductile iron grinding balls, etc. Among them, forged steel balls have good toughness and are not broken when used in large mills. They are the preferred grinding ball varieties in large mills. Although the forged steel ball has a high surface hardness through rapid cooling and quenching, the steel ball lacks a high-hardness and wear-resistant hard phase, so the wear resistance is still difficult to meet the use requirements of large mills.
[0003] In order to improve the performance of steel balls, Chinese invention patent CN113683402A discloses a ceramic composite wear-resistant steel ball, which is characterized in that the ceramic preform is neatly spliced and arranged along the inner surface of the mold, and then a metal melt is cast into the mold, and a ceramic composite wear-resistant steel ball is obtained by heat treatment; wherein the raw materials of the ceramic preform include, by weight: 90 parts of zirconium oxide toughened alumina ceramic particles, 1-3 parts of active powder, 3-4 parts of kaolin, and 3-6 parts of adhesive; the active powder is a combination of nano titanium oxide, nano niobium oxide and nano yttrium oxide; the weight ratio of nano titanium oxide, nano niobium oxide and nano yttrium oxide is 1:0.4-0.6:0.4-0.6; the adhesive is a combination of water glass and carboxymethyl cellulose; the weight ratio of water glass and carboxymethyl cellulose is 1-2:1; in the preparation of the ceramic preform During the process, zirconia toughened alumina ceramic particles, active powder, kaolin, and adhesive aqueous solution are mixed and defoamed, then injected into a mold for shaping, heated to 1200-1300°C at a rate of 3-4°C / min, and sintered for 3-4 hours to obtain a ceramic preform; the raw materials of the metal melt include by weight percentage: C: 1.8-2.0%, Cr: 10.0-11.0%, Mn: 0.5-0.7%, Si: 0.4-0.7%, P≤0.05%, S≤0.05%, and the remainder is Fe and unavoidable impurities; the casting temperature of the metal melt is 1520-1540°C; the heat treatment procedure is: at 890-910°C, keep warm for 2.5-3.5 hours, quench with water, then heat to 220-240°C for tempering for 2-2.5 hours, and cool to room temperature. Chinese invention patent CN103357854A also discloses a ceramic reinforced wear-resistant steel ball, including a reinforcement layer formed by brushing micron-sized ceramic particles on the inner wall of a casting mold and embedding the micron-sized ceramic particles on the surface and sub-surface of the steel ball, and the reinforcement layer and the steel matrix inside the steel ball body form a layered structure from the outside to the inside. The ceramic reinforced wear-resistant steel ball disclosed in the invention has good impact resistance, and has the advantages of high wear resistance, high hardness, and corrosion resistance. It has a larger impact energy under the same grinding conditions, thereby greatly improving the grinding efficiency, without pollution to the grinding material, and ensuring the purity of the grinding material. Chinese invention patent Chinese invention patent CN104084270A also discloses a wear-resistant steel ball, including a steel ball body, the steel ball body is a spherical body with an outer surface composed of multiple regular polygons, the steel ball body includes a surface grinding layer, a strengthening layer and a steel matrix, the surface grinding layer, the strengthening layer and the steel matrix form a layered structure from the outside to the inside, the strengthening layer is formed by a multi-layer system repeatedly coated on the surface of the steel matrix, the multi-layer system includes a metal layer and a ceramic layer, and the surface grinding layer is composed of one or more refractory compound layers. The wear-resistant steel ball disclosed in the invention has good grinding efficiency, and has the advantages of high wear resistance and high hardness.Chinese invention patent CN116947461A also discloses a high iron content wear-resistant ceramic grinding ball, comprising the following raw materials in mass percentage: 5-15% bauxite, 20-60% iron oxide, 20-65% gamma-alumina, 1-5% silicon oxide, 1-10% zirconium oxide, 0.5-5% zinc oxide, 0.1-0.5% chromium oxide, 0.2-3% cerium oxide, 1-5% feldspar, 1-3% talc, 0.5-3% calcium carbonate, 0.2-2% barium carbonate. The invention solves the problem of low-cost production of high-density ceramic grinding balls, the problem of large-scale application of iron oxide leading to a decrease in the wear resistance, strength and hardness of ceramic materials, and the problem of converting iron oxide into spinel mineral AB2X4 with higher hardness at a lower temperature. Chinese invention patent CN117735956A also discloses a high-strength impact-resistant gradient material ceramic grinding ball material, including: N material layers, N≥4; in each material layer, in terms of mass percentage, alumina accounts for 35wt% to 95wt%, and the rest is composite auxiliary materials. The beneficial effects of the present invention are: the powder materials of different layers can all reach the optimal sintering temperature area to sinter densely, with few layer interface defects, and the multi-gradient material grinding ball has a wide specific gravity range, which basically covers the grinding ball demand range of the high energy density grinding method; it can greatly improve the overall toughness, strength and impact resistance of the material; the production cost is low, and it is suitable for industrial mass production; compared with ordinary grinding balls, it can avoid peeling, notching, broken balls and other obvious aggravation of wear in harsh working conditions, and greatly reduce the consumption of grinding balls used in new high-efficiency energy-saving technologies such as semi-autogenous grinding in large mines. Chinese invention patent CN117447189A also discloses a method for preparing ceramic grinding balls using gamma alumina, including the steps of pre-grinding, flocculation, pre-sintering, crushing and rough grinding, molding, drying and sintering. The invention has the following beneficial effects: pre-grinding and pre-sintering treatment of γ-Al2O3, silicon dioxide, talc, calcium carbonate and lanthanum oxide, reducing the high fineness requirements of the molded powder, grinding to obtain powder with a relatively coarse fineness; solid solution strengthening of alumina crystals, forming a solid solution structure LaAlO3, and improving mechanical properties; the added B2O6Zn3 can provide a glass phase to reduce the temperature required for pre-sintering, and can also absorb free Na+ in the Al2O3 structure, avoiding the formation of sodium aluminate to affect the conversion rate of the final corundum phase, avoiding the formation of β-Al2O3, and saving the time for subsequent sintering and densification; using a jet mill to further finely grind the particles, so that the ball blank grows rapidly, which can reduce the difficulty of granulation, save the time of stale homogenization, and effectively improve the molding performance of the powder. Chinese invention patent CN111116183A also discloses a method for preparing alumina ceramic grinding balls, which comprises the following steps: 1) purity ≥ 99.995%, particle size D50 value 0.6-1.0 μm, and specific surface area ≤ 8 m2. 2 / g of alumina powder is sieved to obtain sieved alumina powder; 2) taking the sieved alumina powder, adding pure water of 5%-20% of the weight of the sieved alumina powder, and preparing ball seeds in a ball-forming machine; when the particle size of the ball seeds reaches 0.1-0.3mm, adding sieved alumina powder on the ball seeds in the ball-forming machine to start growing balls; when the ball diameter increases to 0.5-0.6mm, adjusting the ball rolling trajectory, and adding sieved alumina powder to continue growing balls; when the ball diameter increases to 0.7-0.8mm, adjusting the ball rolling trajectory, and adding sieved alumina powder to continue growing balls; when the ball diameter increases to 0.8-0.9mm, the loose density of the alumina balls after ball repair and pressing reaches 1.5g / cm 3 The above; drying and sintering at 1300-1400℃ for 15-25 hours to obtain alumina ceramic grinding balls. The alumina ceramic grinding balls of the invention have the properties of high purity, low wear, high strength, and smooth and rounded surface. Chinese invention patent CN110342902A also discloses a ceramic grinding ball and a preparation method thereof. The ceramic grinding ball is made of the following raw materials in parts by weight: 100 parts of garnet tailings modified material, 17-20 parts of alumina, 0.6-0.8 parts of yttrium oxide, 4.5-5.5 parts of zirconium oxide, 4.5-5.5 parts of kaolin and 4-5 parts of talc; the ceramic grinding balls prepared by the invention have low self-wear, and the preparation method is simple and easy, and the production cost is low. However, the wear-resistant balls produced mainly with ceramic materials are brittle and can usually only be used to produce small-sized grinding balls and are used in small mills. Large-sized grinding balls made mainly of ceramic materials are very brittle and are very easy to crack and peel off when used in large grinding mills, and their excellent wear-resistant properties cannot be fully utilized.
[0004] Chinese invention patent CN115852269A discloses a high-hardness wear-resistant ball for a ball mill and a preparation process thereof, characterized in that it comprises a wear-resistant ball cladding layer and a wear-resistant ball matrix, wherein the cladding layer comprises a composite cladding powder and a ceramic powder, wherein the cladding powder has a particle size of 100-180nm, and comprises, by mass fraction, Cr: 22.3-28.0%, Mo: 5.0-10.0%, W: 4.9-9.7%, Si: 0.3-0.8%, C: 0.009-0.01%, N: 0.0784-0.1734%, and the remainder is cobalt, wherein the weight percentages of molybdenum and tungsten in the metal raw material for preparing the cladding powder are the same; the wear-resistant ball matrix comprises, by mass fraction, C: 0.4-1.3%, Si: 0.55-0.78%, Mn: 1.1-1.42%, Cr: 10 .1~13.42%, Ni: 0.65~0.75%, Cu: 0.4~0.6%, Zr: 0.05~0.15%, Nb: 0.02~0.045%, Mo: 0.4~0.7%, W: 0.3~0.8%, Re: 0.1~0.25%, V: 0.05~0.15%, P≤0.015%, the rest is Fe and unavoidable impurities; the ceramic powder It includes, by mass fraction, C: 0.3-5%, Cr: 8-16%, Co: 0.5-2.5%, Mo: 1-4%, V: 0.5-1.0%, Si: 0.5-3.5%, Mn: 0.5-1%, Ni: 1.5-8%, B: 0.5-4%, P: 0.05-0.1%, the balance is Fe, and Al2O3 with a mass fraction of 3-5% is added as a wear-resistant ceramic phase.Chinese invention patent CN109396396A also discloses a method for preparing an iron-based composite grinding ball, which is characterized by the following steps: (1) mixing raw materials to obtain mixed powder, wherein the raw materials include the following components in weight percentage: 10% dense ZrO2 powder, 22% high carbon ferrochrome powder, 4.5% ferrovanadium powder, 2.5% titanium carbide powder, 3.5% nickel powder and 57.5% reduced iron powder; (2) putting the mixed powder into a ball mill, adding 60mL of anhydrous ethanol per 100g of powder, mixing at a ball mill speed of 100r / min and a mixing time of 36h; (3) putting the mixed powder after ball milling into a vacuum drying oven for drying at a temperature of 250°C and a drying time of 2h; (4) putting the dried mixed powder into a mold for isostatic pressing at a pressure of 300MP and holding the pressure for 0.5h to obtain a ceramic reinforced concrete. (5) hot pressing the ceramic reinforcement body prepared above, the sintering temperature is 1230°C, the pressure is 20MPa, the pressure holding time is 0.5h, and the heat preservation time is 0.5h; (6) the ceramic reinforcement phase in the ceramic reinforcement body contains aluminum oxide, zirconium oxide, vanadium carbide, titanium carbide and chromium carbide, and the thickness of the reinforcement body is 60mm; (7) making a grinding ball sand mold, cutting the ceramic reinforcement body prepared above into a size of Φ20×30mm, and placing it in In the sand mold, the box is assembled; high chromium cast iron is smelted in a medium frequency induction furnace, and the high chromium cast iron composition is C: 3.6%, Cr: 15%, Si: 0.5%, Mn: 0.5%, P: 0.05%, S: 0.0.5%, and the balance is Fe; molten steel is poured in, and the casting temperature is 1560°C. After cooling, an iron-based composite grinding ball embryo is obtained; (8) the iron-based composite grinding ball embryo is heat-treated at 980°C for 1h to obtain an iron-based composite grinding ball. Chinese invention patent CN109265174A also discloses a steel core ceramic grinding ball for a ball mill, comprising a steel ball body, and a ceramic shell is coated on the outside of the steel ball body. The manufacturing method is as follows: first, silicon carbide and boron carbide are mixed and ground into fine powder in a ratio of 9:1, and then spray granulation is performed; the granulated powder is evenly mixed with carbon black, pure water, and a binder in a certain ratio, and the obtained mixed material is isostatically pressed into a hemispherical shell blank; after drying, sintering, and machining, a steel ball is loaded to form a ceramic shell outside the steel ball; after low-temperature drying, the steel ball is naturally cooled to room temperature to obtain a finished steel core ceramic grinding ball. The invention has a simple structure, high strength, and long service life. When used to grind moissanite abrasives, it will not cause material pollution, reduce the subsequent impurity removal cost, and greatly improve production efficiency due to the extended use time. At the same time, the steel core in the replaced waste steel core ceramic grinding ball can also be recycled and reused, reducing production costs. Chinese invention patent CN106914620A and a preparation method for a ceramic / metal composite wear-resistant grinding ball belong to the field of composite materials.The present invention adopts a method combining three-dimensional digital modeling technology with laser selective cladding to prepare a spherical ceramic particle preform with high strength, high porosity, good wettability with molten metal, a certain wall thickness and honeycomb holes, and then uses the preform to be placed in a mold cavity, and prepares a ceramic / metal composite material wear-resistant grinding ball with uniform particle distribution and excellent performance through a pressureless infiltration process. The grinding ball prepared by this method has a low wear rate and a long service life, and can effectively improve the quality and output of the grinding material. Chinese invention patent CN106868418A discloses a low-wear wear-resistant ball for a ball mill and a preparation method thereof, wherein the wear-resistant ball comprises a cladding layer and a wear-resistant ball matrix, and the wear-resistant ball matrix comprises the following components: C, Si, Mn, Cr, Ni, Cu, Al, Mg, B, Ti, Zr, Nb, Mo, Co, V, Nd, W, P, Fe and impurities. In the preparation process, the alloy powder and the ceramic powder are clad on the surface of the wear-resistant ball matrix by laser cladding technology, and the low-wear wear-resistant ball for the ball mill is obtained by pre-cooling treatment, deep cooling treatment, low-temperature tempering, and tempering after cooling treatment. The production of grinding balls by the above method has a complex process and low efficiency. Summary of the invention
[0005] The present invention aims to solve the problems that the existing wear-resistant grinding balls prepared from ceramic particles are brittle, the grinding balls are very easy to crack and peel off when used in large grinding mills, and the excellent wear resistance of the grinding balls cannot be brought into play. The present invention proposes adding a layer of iron-based material to the outer layer of the wear-resistant ceramic particles, and adding the wear-resistant ceramic particles containing the iron-based material to the wear-resistant steel balls, so that the wear-resistant ceramic particles and the steel ball matrix are firmly metallurgically bonded. After forging and heat treatment, the obtained ceramic particle reinforced wear-resistant steel balls have high hardness, excellent wear resistance and impact resistance.
[0006] A ceramic particle reinforced wear-resistant steel ball and a preparation method thereof, wherein the specific preparation process steps include the following steps:
[0007] ①First, use a medium frequency induction furnace to melt hypereutectic high chromium cast iron; use high carbon ferrochrome, medium carbon ferrochrome, carburizer, scrap steel, ferrosilicon and ferroboron as raw materials; first, mix and heat the high carbon ferrochrome, medium carbon ferrochrome, carburizer and scrap steel in a medium frequency induction furnace to melt, add ferrosilicon and ferroboron in sequence after the molten iron is melted, and control the chemical composition and mass fraction of the molten iron in the furnace to 5.58-5.75% C, 36.77-37.61% Cr, 3.62-3.80% Si, 2. 07-2.36% B, <0.50% Mn, the balance is Fe and inevitable impurities; when the temperature of the molten iron in the furnace rises to 1562-1577°C, add 0.13-0.15% of the mass fraction of the molten iron in the furnace with aluminum, keep warm for 3-5 minutes, then remove the molten iron from the furnace and put it into the ladle; rare earth magnesium ferrosilicon alloy blocks and ferrotitanium blocks are placed at the bottom of the ladle in advance, the particle size of the rare earth magnesium ferrosilicon alloy blocks and ferrotitanium blocks are both 3-8mm, and ... The amount of ferrosilicon-magnesium alloy blocks added is 0.45-0.50% of the mass fraction of the molten iron in the ladle, and the amount of ferrotitanium blocks added is 0.30-0.35% of the mass fraction of the molten iron in the ladle; when the molten iron in the ladle is cooled to 1428-1443°C, the molten iron is cast into a water-cooled ingot mold and air-cooled to room temperature to obtain a hypereutectic high-chromium cast iron block; the hypereutectic high-chromium cast iron block is composed of multiple Cr7(C,B)3 ceramic particles + α-Fe metal matrix, wherein The total volume fraction of the ceramic particles is 75-78%. The hypereutectic high chromium cast iron block is first crushed into particles of 25-50 mm by a jaw crusher. The 25-50 mm hypereutectic high chromium cast iron particles are then ground into 150-185 meshes in a ball mill to obtain hypereutectic high chromium cast iron powder. The obtained hypereutectic high chromium cast iron powder is wear-resistant ceramic particles having a layer of iron-based material on the outer layer, and further Cr7(C,B)3 ceramic particles having an α-Fe metal matrix on the outer surface.
[0008] ② Use medium frequency induction furnace to melt molten steel for wear-resistant steel balls, use scrap steel, scrap copper, carburizer, ferrochrome, ferrosilicon, and ferromanganese as ingredients, first mix scrap steel, carburizer and ferrochrome and heat to melt, add ferrosilicon, scrap copper and ferromanganese in sequence after the molten steel is melted, and control the chemical composition and mass fraction of the molten steel in the furnace to 0.62-0.71% C, 0.55-0.76% Si, 0.87-0.99% Mn, 0.63-0.74% Cu, 0.58-0.72% Cr, <0.040% S, <0.045% P, the remainder is Fe and unavoidable impurity elements; heat the molten steel in the furnace to When the temperature is 1641-1658°C, adding metal aluminum accounting for 0.10-0.12% of the mass fraction of the molten steel in the furnace, keeping the temperature for 4-5 minutes, and then discharging the molten steel into the ladle in two times; when the mass fraction of the molten steel entering the ladle for the first time accounts for 28-40% of the total amount of the molten steel entering the ladle, the hypereutectic high chromium cast iron powder obtained in step ① is preheated at 950-980°C for 120-150 minutes and then added into the ladle, and the mass fraction of the hypereutectic high chromium cast iron powder added accounts for 10-12% of the total amount of the molten steel entering the ladle; after all the hypereutectic high chromium cast iron powder enters the ladle, the remaining molten steel in the electric furnace is discharged into the ladle;
[0009] ③ When the temperature of the molten steel in the ladle drops to 1506-1521°C, pour it into the crystallizer on the continuous casting machine, and during the continuous casting process, the molten steel in the crystallizer is electromagnetically stirred, the electromagnetic stirring current is 380-400A, and the electromagnetic stirring frequency is 4-5Hz; the continuous casting machine pulling speed is 0.65-0.70m / min; cast into round steel bars with a diameter of φ80-90mm, and the length of the round steel bars is cut into 6-8m; then the round steel bars with a length of 6-8m are placed in a heating furnace for heating, and after the round steel bars are uniformly heated to 1180-1220°C and kept warm for 45-60 minutes, the round steel bars are transported to the continuous cutting machine through a steel bar conveying device with a heat preservation device for cutting to obtain steel sections; then the steel sections are forged into steel balls, and the final forging temperature is controlled at 950-1050°C;
[0010] ④ When the surface of the steel ball is air-cooled to 825-850°C, the steel ball is sent to a quenching water pool at 28-45°C for quenching; the volume ratio of water to steel ball in the quenching water pool is greater than 10:1; when the surface temperature of the steel ball drops to 90-120°C, it is taken out and immediately placed in a heat treatment furnace at a temperature of 180-210°C for 18-19 hours, and then cooled to a temperature below 135°C; finally, it is taken out of the furnace and air-cooled to room temperature to obtain a ceramic particle reinforced wear-resistant steel ball.
[0011] As mentioned above, the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy block are: 6.14-7.88% RE, 3.36-4.21% Mg, 38.62-41.17% Si, ≤1% Ti, ≤1% Al, and the remainder is Fe and unavoidable impurity elements.
[0012] As mentioned above, the chemical composition and mass fraction of the titanium iron block are: 29.61-30.86% Ti, <8.5% Al, <5.0% Si, and the remainder is Fe and unavoidable impurity elements.
[0013] The present invention is mainly to solve the problems that the wear-resistant grinding balls prepared from ceramic particles are brittle, the grinding balls are very easy to crack and peel off when used in large grinding mills, and the excellent wear resistance of the grinding balls cannot be brought into play. The present invention proposes to add a layer of iron-based material to the outer layer of the wear-resistant ceramic particles, and add the wear-resistant ceramic particles containing the iron-based material to the wear-resistant steel balls, so that the wear-resistant ceramic particles and the steel ball matrix are firmly metallurgically bonded. After forging and heat treatment, the obtained ceramic particle reinforced wear-resistant steel balls have high hardness, excellent wear resistance and impact resistance. A ceramic particle reinforced wear-resistant steel ball and a preparation method thereof, the specific preparation process steps are:
[0014] The first step is to prepare wear-resistant ceramic particles. First, high carbon ferrochrome, medium carbon ferrochrome, carburizer, scrap steel, ferrosilicon and ferroboron are used as raw materials to melt hypereutectic high chromium cast iron in a medium frequency induction furnace. The purpose is to obtain Cr7(C,B)3 ceramic material + Fe metal matrix. The invention firstly mixes high carbon ferrochrome, medium carbon ferrochrome, carburizer and scrap steel in a medium frequency induction furnace for heating and melting, and sequentially adds ferrosilicon and ferroboron after the molten iron is melted, and controls the chemical composition and mass fraction of the molten iron in the furnace to be 5.58-5.75% C, 36.77-37.61% Cr, 3.62-3.80% Si, 2.07-2.36% B, <0.50% Mn, and the remainder is Fe and inevitable impurity elements; when the molten iron in the furnace is heated to 1562-1577°C, metal aluminum accounting for 0.13-0.15% of the mass fraction of the molten iron in the furnace is added, and after keeping the temperature for 3-5 minutes, the molten iron is subjected to slagging treatment, and then taken out of the furnace and poured into a ladle. The molten iron of the present invention contains 5.58-5.75% C, 36.77-37.61% Cr and 2.07-2.36% B. During the solidification of the molten iron, a high-hardness Cr7(C, B)3 ceramic material + Fe metal matrix can be generated. The melting point of Cr7(C, B)3 is 1890°C and the boiling point is 3800°C, which also shows its stability at high temperatures. The microhardness of Cr7(C, B)3 is as high as 2200-2700kg / mm 2 , which is significantly higher than the hardness of Fe3C, exists in the steel ball matrix and can significantly improve the wear resistance of the steel ball. In addition, the density of Cr7(C,B)3 is 6.68g / cm 3, and the density of molten steel (the density of molten steel is generally 7.0g / cm 3 ) is close to that of titanium carbide, and will not cause significant segregation when added to molten steel. The density of common wear-resistant hard phase titanium carbide is 4.93g / cm 3 , which is significantly lower than the density of molten steel. It is very easy to cause segregation when added to wear-resistant steel, and the excellent wear-resistant effect of the wear-resistant hard phase cannot be exerted.
[0015] The present invention also adds 3.62-3.80% Si, which is an element that shrinks the γ phase region, and the manganese content in the present invention is less than 0.50%, which ensures that the solidified matrix structure of the hypereutectic high chromium cast iron is low-strength α-Fe ferrite, which is conducive to the subsequent crushing and grinding process of the hypereutectic high chromium cast iron block after solidification, and it is easy to obtain 150-185 mesh hypereutectic high chromium cast iron powder. The Cr7(C, B)3 phase microstructure of ordinary hypereutectic high chromium cast iron after solidification is coarse. When the processed powder is used for the production of wear-resistant steel balls, the steel balls are brittle and easy to break during use. The excellent wear resistance of the steel balls cannot be brought into play. The present invention pre-places rare earth magnesium ferrosilicon alloy blocks (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy blocks are: 6.14-7.88% RE, 3.36-4.21% Mg, 38.62-41.17% Si, ≤1% Ti, ≤1% Al, and the balance is Fe and unavoidable impurity elements) and ferrotitanium blocks (the chemical composition and mass fraction of the ferrotitanium blocks are: 29.61-30.86% Ti, <8.5% Al, <5. 0% Si, the balance is Fe and unavoidable impurity elements), the particle size of rare earth magnesium ferrosilicon alloy block and ferrotitanium block is 3-8mm, the amount of rare earth magnesium ferrosilicon alloy block added accounts for 0.45-0.50% of the mass fraction of molten iron entering the ladle; the amount of ferrotitanium block added accounts for 0.30-0.35% of the mass fraction of molten iron entering the ladle; when the molten iron in the ladle is cooled to 1428-1443°C, the molten iron is cast into a water-cooled ingot mold, and finally air-cooled to room temperature to obtain a hypereutectic high-chromium cast iron block. The present invention achieves significant refinement of the Cr7(C,B)3 phase in the hypereutectic high-chromium cast iron block. The hypereutectic high-chromium cast iron block of the present invention is composed of Cr7(C,B)3 ceramic particles with a volume fraction of 75-78% + α-Fe metal matrix. Multiple Cr7(C,B)3 ceramic particles + α-Fe metal matrix are combined into one, and multiple Cr7(C,B)3 ceramic particles are tightly wrapped by the α-Fe metal matrix into one, which is a strong metallurgical combination. The present invention continues to crush the hypereutectic high chromium cast iron block into particles of 25 to 50 mm with a jaw crusher; then grind the 25 to 50 mm hypereutectic high chromium cast iron particles into 150 to 185 meshes in a ball mill to obtain hypereutectic high chromium cast iron (Cr7(C,B)3 ceramic material + α-Fe metal matrix) powder.
[0016] The second step is to use a medium frequency induction furnace to melt the molten steel of the wear-resistant steel balls, using scrap steel, scrap copper, carburizer, ferrochrome, ferrosilicon, and ferromanganese as ingredients. The sources of scrap steel, scrap copper, carburizer, ferrochrome, ferrosilicon, ferromanganese and other furnace materials are convenient and inexpensive. The present invention first mixes scrap steel, carburizer and ferrochrome for heating and melting, and then adds ferrosilicon, scrap copper and ferromanganese in sequence after the molten steel is melted, and controls the chemical composition and mass fraction of the molten steel in the furnace to 0.62-0.71% C, 0.55-0.76% Si, 0.87-0.99% Mn, 0.63-0.74% Cu, 0.58-0.72% Cr, <0.040% S, <0.045% P, and the remainder is Fe and unavoidable impurity elements. The steel ball matrix of the present invention contains 0.63-0.74% Cu and 0.58-0.72% Cr, which can significantly improve the hardenability of the steel ball. When the molten steel in the furnace is heated to 1641-1658°C, 0.10-0.12% of metal aluminum is added to the molten steel by mass, and after keeping the temperature for 4-5 minutes, the molten steel is discharged from the furnace into a ladle in two batches.
[0017] When the mass fraction of molten steel entering the ladle for the first time accounts for 28-40% of the total amount of molten steel entering the ladle, the previously obtained hypereutectic high chromium cast iron powder, which is composed of Cr7(C,B)3 ceramic material + α-Fe metal matrix, is added to the ladle after preheating at 950-980°C for 120-150 minutes. The mass fraction of hypereutectic high chromium cast iron powder added accounts for 10-12% of the total amount of molten steel entering the ladle. After all the hypereutectic high chromium cast iron powder enters the ladle, the remaining molten steel in the electric furnace is discharged into the ladle. When the temperature of the molten steel in the ladle drops to 1506-1521°C, it is poured into the crystallizer on the continuous casting machine, and the molten steel in the crystallizer is electromagnetically stirred during the continuous casting process of the molten steel. The electromagnetic stirring current is 380-400A, the electromagnetic stirring frequency is 4-5Hz, and the continuous casting machine pulling speed is 0.65-0.70m / min, and it is cast into a round steel bar with a diameter of φ80-90mm. Electromagnetic stirring changes the flow, heat transfer and mass transfer during the solidification process by strengthening the movement of the unsolidified molten metal in the ingot (round steel bar), thereby achieving the purpose of refining the grains and improving the quality of the ingot. In addition, electromagnetic stirring can also increase the equiaxed crystal area ratio of the ingot, reduce the non-metallic inclusions on the surface, and alleviate the segregation and looseness, thereby further improving the quality of the ingot. The addition of electromagnetic stirring during the solidification process of the present invention can also promote the uniform distribution of hypereutectic high-chromium cast iron powder in the steel. Since the melting point of Cr7(C,B)3 is as high as 1890°C, Cr7(C,B)3 will not melt when added to molten steel at 1641-1658°C. However, the α-Fe metal matrix around Cr7(C,B)3 will melt, promoting the final Cr7(C,B)3 phase in the round steel bar after continuous casting to achieve a firm metallurgical bond with the metal matrix in the steel bar.
[0018] The present invention cuts the length of the round steel rod into 6-8m; then the round steel rod with a length of 6-8m is placed in a heating furnace for heating, and after the round steel rod is evenly heated to 1180-1220°C and kept warm for 45-60 minutes, the round steel rod is transported to a continuous cutting machine through a steel rod conveying device with a heat preservation device for cutting to obtain a steel section. Then the steel section is forged into a steel ball, and the final forging temperature is controlled at 950-1050°C. The grinding ball is processed by the forging method, and the grinding ball has a dense structure and further improved performance. Since the Cr7(C, B)3 phase is small in size and is firmly metallurgically bonded to the metal matrix in the steel rod, the Cr7(C, B)3 phase will not crack even during the forging process.
[0019] Finally, when the surface of the steel ball is air-cooled to 825-850°C, the steel ball needs to be sent to a quenching water pool at 28-45°C for quenching; the volume ratio of water to steel ball in the quenching water pool is greater than 10:1. The rapid quenching of the steel ball is mainly to obtain a high-hardness martensitic matrix and prevent the appearance of a low-hardness pearlite microstructure. However, the water quenching time of the steel ball must be strictly controlled. If the water quenching time is too long, the internal stress of the steel ball will be too large, and the steel ball is very likely to crack. When the surface temperature of the steel ball drops to 90-120°C, the steel ball needs to be taken out immediately, and immediately placed in a heat treatment furnace at a temperature of 180-210°C for 18-19 hours to eliminate the internal stress of the steel ball, and then the furnace is cooled to a temperature below 135°C, and finally taken out of the furnace and air-cooled to room temperature, ceramic particle reinforced wear-resistant steel balls can be obtained.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) The ceramic particle reinforced wear-resistant steel ball of the present invention has less precious alloy content and low cost;
[0022] (2) The ceramic particle reinforced wear-resistant steel ball of the present invention contains high-hardness fine Cr7(C,B)3 ceramic particles with a volume fraction exceeding 8%, good hardenability, high hardenability, no quenching soft spot, the surface hardness of the steel ball exceeds 65HRC, the core hardness exceeds 63HRC, and the impact toughness exceeds 22J / cm 2 ;
[0023] (3) The ceramic particle reinforced wear-resistant steel ball of the present invention has a fine and dense microstructure and excellent anti-drop performance. After being dropped 2500 times continuously on an 8m grinding ball drop tester, the grinding ball of the present invention does not crack or peel off, indicating that the grinding ball has a strong ability to resist impact fatigue damage.
[0024] (4) The ceramic particle reinforced wear-resistant steel ball of the present invention is used in large-scale semi-autogenous grinding mills in large-scale copper, gold, nickel and other non-ferrous metal beneficiation industries. The grinding ball of the present invention does not lose roundness, crack or peel off, and has excellent wear resistance. Under the same wear conditions, the wear rate of the grinding ball of the present invention is reduced by more than 45% compared with the forged 65Mn grinding ball. The promotion of the wear-resistant steel ball of the present invention has good economic and social benefits. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below with reference to the examples, but the present invention is not limited to the following examples.
[0026] Embodiment 1:
[0027] A ceramic particle reinforced wear-resistant steel ball and a preparation method thereof, characterized in that wear-resistant ceramic particles are added to the wear-resistant steel ball to achieve a firm metallurgical bond between the wear-resistant ceramic particles and the steel ball matrix. After forging and heat treatment, the obtained ceramic particle reinforced wear-resistant steel ball has high hardness, excellent wear resistance and impact resistance. The specific preparation process steps are:
[0028] ① First, use a medium frequency induction furnace to melt hypereutectic high chromium cast iron; use high carbon ferrochrome, medium carbon ferrochrome, carburizer, scrap steel, ferrosilicon and ferroboron as raw materials; first, mix and heat the high carbon ferrochrome, medium carbon ferrochrome, carburizer and scrap steel in a medium frequency induction furnace to melt, and add ferrosilicon and ferroboron in sequence after the molten iron is melted, and control the chemical composition and mass fraction of the molten iron in the furnace to 5.64% C, 36.92% Cr, 3.75% Si, 2.29% B, 0.37% Mn, and the remainder is Fe and non-ferrous metals. When the temperature of the molten iron in the furnace rises to 1571°C, 0.14% of the metal aluminum by mass fraction is added to the molten iron in the furnace. After keeping the temperature for 4 minutes, the molten iron is slag-treated and then taken out of the furnace into a ladle. A rare earth magnesium ferrosilicon alloy block is placed at the bottom of the ladle (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy block are: 6.96% RE, 3.80% Mg, 39.58% Si, 0.73% Ti, 0.51% Al, and the remainder is Fe and unavoidable impurity elements; when the temperature of the molten iron in the furnace rises to 1571°C, 0.14% of the metal aluminum by mass fraction is added to the molten iron in the furnace. After keeping the temperature for 4 minutes, the molten iron is slag-treated and then taken out of the furnace into a ladle. The ferrotitanium block is composed of 29.97% Ti, 7.05% Al, 2.49% Si, and the remainder is Fe and unavoidable impurity elements. The particle size of the rare earth magnesium ferrosilicon alloy block and the ferrosilicon alloy block is 3-8 mm. The amount of the rare earth magnesium ferrosilicon alloy block added accounts for 0.48% of the mass fraction of the molten iron entering the ladle; the amount of the ferrosilicon block added accounts for 0.32% of the mass fraction of the molten iron entering the ladle. When the molten iron in the ladle cools down, When the temperature reaches 1436°C, the molten iron is cast into a water-cooled ingot mold and air-cooled to room temperature to obtain a hypereutectic high-chromium cast iron block; the hypereutectic high-chromium cast iron block is composed of Cr7(C,B)3 ceramic particles with a volume fraction of 75-78% + α-Fe metal matrix; the hypereutectic high-chromium cast iron block is first crushed into particles of 25-50 mm by a jaw crusher; and the 25-50 mm hypereutectic high-chromium cast iron particles are then ground into 150-185 meshes in a ball mill to obtain a hypereutectic high-chromium cast iron powder;
[0029] ② Use medium frequency induction furnace to melt molten steel for wear-resistant steel balls, use scrap steel, scrap copper, carburizer, ferrochrome, ferrosilicon and ferromanganese as ingredients, first mix scrap steel, carburizer and ferrochrome and heat to melt, add ferrosilicon, scrap copper and ferromanganese in turn after the molten steel is melted, and control the chemical composition and mass fraction of the molten steel in the furnace to 0.67% C, 0.65% Si, 0.92% Mn, 0.68% Cu, 0.63% Cr, 0.029% S, 0.042% P, and the remainder is Fe and unavoidable impurity elements; heat the molten steel in the furnace to 16 When the temperature is 53°C, 0.11% of the mass fraction of the molten steel in the furnace is added with aluminum. After keeping the temperature for 4.5 minutes, the molten steel is discharged into the ladle in two times. When the mass fraction of the molten steel entering the ladle accounts for 28% of the total amount of the molten steel entering the ladle, the hypereutectic high chromium cast iron powder obtained in step ① is preheated at 960°C for 130 minutes and then added into the ladle. The mass fraction of the hypereutectic high chromium cast iron powder added accounts for 11% of the total amount of the molten steel entering the ladle. After all the hypereutectic high chromium cast iron powder enters the ladle, the rest of the molten steel in the electric furnace is discharged into the ladle.
[0030] ③ When the temperature of the molten steel in the ladle drops to 1517℃, it is poured into the crystallizer on the continuous casting machine, and the molten steel in the crystallizer is electromagnetically stirred during the continuous casting process, the electromagnetic stirring current is 390A, and the electromagnetic stirring frequency is 4.5Hz; the continuous casting machine pulling speed is 0.68m / min; it is cast into a round steel bar with a diameter of φ90mm, and the length of the round steel bar is cut into 7m; then the round steel bar with a length of 7m is placed in a heating furnace for heating, and after the round steel bar is evenly heated to 1200℃ and kept warm for 50 minutes, the round steel bar is transported to a continuous cutting machine through a steel bar conveying device with a heat preservation device for cutting to obtain a steel segment with a length of 180.8mm; then the steel segment is forged into a φ130mm steel ball, and the final forging temperature is controlled at 950~1050℃;
[0031] ④ When the surface of the steel ball is air-cooled to 830-845℃, the steel ball is sent to a quenching water pool at 37℃ for quenching; the volume ratio of water to steel ball in the quenching water pool is greater than 10:1; when the surface temperature of the steel ball drops to 90-120℃, it is taken out and immediately placed in a heat treatment furnace at 200℃ for 18.5 hours, and then the furnace is cooled to a temperature below 135℃; finally, it is taken out of the furnace and air-cooled to room temperature to obtain a ceramic particle reinforced wear-resistant steel ball. The mechanical properties of the wear-resistant steel ball are shown in Table 1.
[0032] Embodiment 2:
[0033] A ceramic particle reinforced wear-resistant steel ball and a preparation method thereof, characterized in that wear-resistant ceramic particles are added to the wear-resistant steel ball to achieve a firm metallurgical bond between the wear-resistant ceramic particles and the steel ball matrix. After forging and heat treatment, the obtained ceramic particle reinforced wear-resistant steel ball has high hardness, excellent wear resistance and impact resistance. The specific preparation process steps are:
[0034] ① First, use a medium frequency induction furnace to melt hypereutectic high chromium cast iron; use high carbon ferrochrome, medium carbon ferrochrome, carburizer, scrap steel, ferrosilicon and ferroboron as raw materials; first, mix and heat the high carbon ferrochrome, medium carbon ferrochrome, carburizer and scrap steel in a medium frequency induction furnace to melt, and add ferrosilicon and ferroboron in sequence after the molten iron is melted, and control the chemical composition and mass fraction of the molten iron in the furnace to 5.58% C, 37.61% Cr, 3.80% Si, 2.36% B, 0.44% Mn, and the remainder is Fe and non-ferrous metals. When the temperature of the molten iron in the furnace rises to 1562°C, 0.13% of the metal aluminum by mass fraction is added to the molten iron in the furnace. After keeping the temperature for 5 minutes, the molten iron is slag-treated and then taken out of the furnace into a ladle. A rare earth magnesium ferrosilicon alloy block is placed at the bottom of the ladle (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy block are: 6.14% RE, 4.21% Mg, 38.62% Si, 0.41% Ti, 0.67% Al, and the remainder is Fe and unavoidable impurity elements; when the temperature of the molten iron in the furnace rises to 1562°C, 0.13% of the metal aluminum by mass fraction is added to the molten iron in the furnace. After keeping the temperature for 5 minutes, the molten iron is slag-treated and then taken out of the furnace into a ladle. The ferrotitanium block is composed of 29.61% Ti, 4.53% Al, 2.88% Si, and the remainder is Fe and unavoidable impurity elements. The particle size of the rare earth magnesium ferrosilicon alloy block and the ferrosilicon alloy block is 3-8 mm. The amount of the rare earth magnesium ferrosilicon alloy block added accounts for 0.45% of the mass fraction of the molten iron entering the ladle; the amount of the ferrosilicon block added accounts for 0.35% of the mass fraction of the molten iron entering the ladle. When the molten iron in the ladle cools down, When the temperature reaches 1428°C, the molten iron is cast into a water-cooled ingot mold and air-cooled to room temperature to obtain a hypereutectic high-chromium cast iron block; the hypereutectic high-chromium cast iron block is composed of Cr7(C,B)3 ceramic particles with a volume fraction of 75-78% + α-Fe metal matrix; the hypereutectic high-chromium cast iron block is first crushed into particles of 25-50 mm by a jaw crusher; and the 25-50 mm hypereutectic high-chromium cast iron particles are then ground into 150-185 meshes in a ball mill to obtain a hypereutectic high-chromium cast iron powder;
[0035] ② Use medium frequency induction furnace to melt molten steel for wear-resistant steel balls, use scrap steel, scrap copper, carburizer, ferrochrome, ferrosilicon, and ferromanganese as ingredients, first mix scrap steel, carburizer and ferrochrome and heat to melt, add ferrosilicon, scrap copper and ferromanganese in sequence after the molten steel is melted, and control the chemical composition and mass fraction of the molten steel in the furnace to 0.62% C, 0.76% Si, 0.87% Mn, 0.74% Cu, 0.58% Cr, 0.029% S, 0.043% P, and the remainder is Fe and unavoidable impurity elements; heat the molten steel in the furnace to 1 When the temperature is 641°C, 0.10% of the mass fraction of the molten steel in the furnace is added with aluminum. After keeping the temperature for 5 minutes, the molten steel is discharged into the ladle in two times. When the mass fraction of the molten steel entering the ladle accounts for 40% of the total amount of the molten steel entering the ladle, the hypereutectic high chromium cast iron powder obtained in step ① is preheated at 950°C for 150 minutes and then added into the ladle. The mass fraction of the hypereutectic high chromium cast iron powder added accounts for 10% of the total amount of the molten steel entering the ladle. After all the hypereutectic high chromium cast iron powder enters the ladle, the rest of the molten steel in the electric furnace is discharged into the ladle.
[0036] ③ When the temperature of the molten steel in the ladle drops to 1506℃, it is poured into the crystallizer on the continuous casting machine, and the molten steel in the crystallizer is electromagnetically stirred during the continuous casting process, the electromagnetic stirring current is 380A, and the electromagnetic stirring frequency is 4Hz; the continuous casting machine pulling speed is 0.65m / min; it is cast into a round steel bar with a diameter of φ80mm, and the length of the round steel bar is cut into 6m; then the round steel bar with a length of 6m is placed in a heating furnace for heating, and after the round steel bar is evenly heated to 1180℃ and kept warm for 60 minutes, the round steel bar is transported to a continuous cutting machine through a steel bar conveying device with a heat preservation device for cutting to obtain a steel segment with a length of 180.0mm; then the steel segment is forged into a φ120mm steel ball, and the final forging temperature is controlled at 950~1050℃;
[0037] ④ When the surface of the steel ball is air-cooled to 825-840℃, the steel ball is sent to a quenching water pool at 28℃ for quenching; the volume ratio of water to steel ball in the quenching water pool is greater than 10:1; when the surface temperature of the steel ball drops to 90-120℃, it is taken out and immediately placed in a heat treatment furnace at 180℃ for 19 hours, and the furnace is cooled to a temperature below 135℃; finally, it is taken out of the furnace and air-cooled to room temperature to obtain a ceramic particle reinforced wear-resistant steel ball. The mechanical properties of the wear-resistant steel ball are shown in Table 1.
[0038] Embodiment 3:
[0039] A ceramic particle reinforced wear-resistant steel ball and a preparation method thereof, characterized in that wear-resistant ceramic particles are added to the wear-resistant steel ball to achieve a firm metallurgical bond between the wear-resistant ceramic particles and the steel ball matrix. After forging and heat treatment, the obtained ceramic particle reinforced wear-resistant steel ball has high hardness, excellent wear resistance and impact resistance. The specific preparation process steps are:
[0040] ① First, use a medium frequency induction furnace to melt hypereutectic high chromium cast iron; use high carbon ferrochrome, medium carbon ferrochrome, carburizer, scrap steel, ferrosilicon and ferroboron as raw materials; first, mix and heat the high carbon ferrochrome, medium carbon ferrochrome, carburizer and scrap steel in a medium frequency induction furnace to melt, and add ferrosilicon and ferroboron in sequence after the molten iron is melted, and control the chemical composition and mass fraction of the molten iron in the furnace to 5.75% C, 36.77% Cr, 3.80% Si, 2.07% B, 0.42% Mn, and the remainder is Fe and non-ferrous metals. When the temperature of the molten iron in the furnace rises to 1577°C, 0.15% of the metal aluminum by mass fraction is added to the molten iron in the furnace. After keeping the temperature for 3 minutes, the molten iron is slag-treated and then taken out of the furnace into a ladle. A rare earth magnesium ferrosilicon alloy block is placed at the bottom of the ladle (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy block are: 7.88% RE, 3.36% Mg, 41.17% Si, 0.67% Ti, 0.38% Al, and the remainder is Fe and unavoidable impurity elements; when the temperature of the molten iron in the furnace rises to 1577°C, 0.15% of the metal aluminum by mass fraction is added to the molten iron in the furnace. After keeping the temperature for 3 minutes, the molten iron is slag-treated and then taken out of the furnace into a ladle. The ferrotitanium block is composed of 30.86% Ti, 3.69% Al, 3.04% Si, and the remainder is Fe and unavoidable impurity elements. The particle size of the rare earth magnesium ferrosilicon alloy block and the ferrosilicon alloy block is 3-8 mm. The amount of the rare earth magnesium ferrosilicon alloy block added accounts for 0.50% of the mass fraction of the molten iron entering the ladle; the amount of the ferrosilicon block added accounts for 0.30% of the mass fraction of the molten iron entering the ladle. When the molten iron in the ladle cools down, When the temperature reaches 1443°C, the molten iron is cast into a water-cooled ingot mold and air-cooled to room temperature to obtain a hypereutectic high-chromium cast iron block; the hypereutectic high-chromium cast iron block is composed of Cr7(C,B)3 ceramic particles with a volume fraction of 75-78% + α-Fe metal matrix; the hypereutectic high-chromium cast iron block is first crushed into particles of 25-50 mm by a jaw crusher; and the 25-50 mm hypereutectic high-chromium cast iron particles are then ground into 150-185 meshes in a ball mill to obtain a hypereutectic high-chromium cast iron powder;
[0041] ② Use medium frequency induction furnace to melt molten steel for wear-resistant steel balls, use scrap steel, scrap copper, carburizer, ferrochrome, ferrosilicon, and ferromanganese as ingredients, first mix scrap steel, carburizer and ferrochrome and heat to melt, add ferrosilicon, scrap copper and ferromanganese in sequence after the molten steel is melted, and control the chemical composition and mass fraction of the molten steel in the furnace to 0.71% C, 0.55% Si, 0.99% Mn, 0.63% Cu, 0.72% Cr, 0.035% S, 0.040% P, and the remainder is Fe and unavoidable impurity elements; heat the molten steel in the furnace to 1 At 658°C, adding 0.12% of the mass fraction of the molten steel in the furnace with aluminum, keeping the temperature for 4 minutes, and then discharging the molten steel into the ladle in two times; when the mass fraction of the molten steel entering the ladle for the first time accounts for 37% of the total amount of the molten steel entering the ladle, the hypereutectic high chromium cast iron powder obtained in step ① is added into the ladle after being preheated at 980°C for 120 minutes, and the mass fraction of the hypereutectic high chromium cast iron powder added accounts for 12% of the total amount of the molten steel entering the ladle; after all the hypereutectic high chromium cast iron powder enters the ladle, the rest of the molten steel in the electric furnace is discharged into the ladle;
[0042] ③ When the temperature of the molten steel in the ladle drops to 1521°C, it is poured into the crystallizer on the continuous casting machine, and the molten steel in the crystallizer is electromagnetically stirred during the continuous casting process, the electromagnetic stirring current is 400A, and the electromagnetic stirring frequency is 5Hz; the continuous casting machine pulling speed is 0.70m / min; it is cast into a round steel bar with a diameter of φ85mm, and the length of the round steel bar is cut into 8m; then the round steel bar with a length of 8m is placed in a heating furnace for heating, and after the round steel bar is evenly heated to 1220°C and kept warm for 45 minutes, the round steel bar is transported to a continuous cutting machine through a steel bar conveying device with a heat preservation device for cutting to obtain a steel segment with a length of 180.2mm; then the steel segment is forged into a φ125mm steel ball, and the final forging temperature is controlled at 950-1050°C;
[0043] ④ When the surface of the steel ball is air-cooled to 835-850℃, the steel ball is sent to a quenching water pool at 45℃ for quenching; the volume ratio of water to steel ball in the quenching water pool is greater than 10:1; when the surface temperature of the steel ball drops to 90-120℃, it is taken out and immediately placed in a heat treatment furnace at 210℃ for 18 hours, and the furnace is cooled to a temperature below 135℃. Finally, it is taken out of the furnace and air-cooled to room temperature to obtain a ceramic particle reinforced wear-resistant steel ball. The mechanical properties of the wear-resistant steel ball are shown in Table 1.
[0044] Table 1 Mechanical properties of wear-resistant steel balls
[0045]
[0046] The ceramic particle reinforced wear-resistant steel ball of the present invention has less precious alloy content and low cost. The ceramic particle reinforced wear-resistant steel ball of the present invention contains high-hardness fine Cr7(C,B)3 ceramic particles with a volume fraction exceeding 8%, good hardenability, high hardenability, no quenching soft spot, the surface hardness of the steel ball exceeds 65HRC, the core hardness exceeds 63HRC, and the impact toughness exceeds 22J / cm 2 . The ceramic particle reinforced wear-resistant steel ball of the present invention has a fine and dense microstructure and has excellent anti-drop performance. The grinding ball dropped 2500 times continuously on an 8m drop ball drop test machine without obvious cracking of the ball or large surface peeling, which is far higher than the customer's requirement of 1200 times, indicating that the grinding ball has a strong ability to resist impact fatigue damage. The ceramic particle reinforced wear-resistant steel ball of the present invention is used in large-scale semi-autogenous grinding mills in large-scale copper mines, gold mines, nickel mines and other non-ferrous metal beneficiation industries. It does not lose roundness, crack or peel off, and has excellent wear resistance. Under the same wear conditions, the wear rate of the grinding ball of the present invention is reduced by more than 45% compared with the forged 65Mn grinding ball. The promotion and application of the ceramic particle reinforced wear-resistant steel ball of the present invention has good economic and social benefits.
Claims
1. A method for preparing a ceramic particle reinforced wear-resistant steel ball, It is characterized in that The specific steps include: ① First, use a medium frequency induction furnace to melt hypereutectic high chromium cast iron; use high carbon ferrochrome, medium carbon ferrochrome, carburizer, scrap steel, ferrosilicon and ferroboron as raw materials; first, mix and heat the high carbon ferrochrome, medium carbon ferrochrome, carburizer and scrap steel in a medium frequency induction furnace to melt, add ferrosilicon and ferroboron in sequence after the molten iron is melted, and control the chemical composition and mass fraction of the molten iron in the furnace to 5.58-5.75% C, 36.77-37.61% Cr, 3.62-3.80% Si, 2.07-2.36% B, <0.50% Mn, and the remainder is Fe and unavoidable impurity elements; when the molten iron in the furnace is heated to 1562-1577℃, add 2% of the mass fraction of the molten iron in the furnace. 0.13-0.15% of metallic aluminum is added, and after keeping warm for 3-5 minutes, the molten iron is slag-scraped and then taken out of the furnace into a ladle; rare earth magnesium ferrosilicon alloy blocks and ferrotitanium blocks are placed at the bottom of the ladle in advance, and the particle sizes of the rare earth magnesium ferrosilicon alloy blocks and ferrotitanium blocks are both 3-8 mm, and the amount of rare earth magnesium ferrosilicon alloy blocks added accounts for 0.45-0.50% of the mass fraction of the molten iron entering the ladle, and the amount of ferrotitanium blocks added accounts for 0.30-0.35% of the mass fraction of the molten iron entering the ladle; when the molten iron in the ladle is cooled to 1428-1443°C, the molten iron is cast into a water-cooled ingot mold and air-cooled to room temperature to obtain a hypereutectic high chromium cast iron block; the hypereutectic high chromium cast iron block consists of multiple Cr 7 (C,B) 3 The invention discloses a method for preparing a hypereutectic high chromium cast iron powder. The method comprises a ceramic particle and an α-Fe metal matrix, wherein the ceramic particle accounts for 75 to 78% of the total volume fraction. The hypereutectic high chromium cast iron block is first crushed into particles of 25 to 50 mm by a jaw crusher. The hypereutectic high chromium cast iron particles of 25 to 50 mm are then ground into 150 to 185 meshes in a ball mill to obtain a hypereutectic high chromium cast iron powder. The obtained hypereutectic high chromium cast iron powder is a wear-resistant ceramic particle having an outer layer of an iron-based material, and further a Cr-based material having an α-Fe metal matrix on the outer surface. 7 (C,B) 3 Ceramic particles; ② Use medium frequency induction furnace to melt molten steel for wear-resistant steel balls, use scrap steel, scrap copper, carburizer, ferrochrome, ferrosilicon, and ferromanganese as ingredients, first mix scrap steel, carburizer and ferrochrome and heat to melt, add ferrosilicon, scrap copper and ferromanganese in sequence after the molten steel is melted, and control the chemical composition and mass fraction of the molten steel in the furnace to 0.62-0.71% C, 0.55-0.76% Si, 0.87-0.99% Mn, 0.63-0.74% Cu, 0.58-0.72% Cr, <0.040% S, <0.045% P, the remainder is Fe and unavoidable impurity elements; heat the molten steel in the furnace to When the temperature is 1641-1658°C, adding metal aluminum accounting for 0.10-0.12% of the mass fraction of the molten steel in the furnace, keeping the temperature for 4-5 minutes, and then discharging the molten steel into the ladle in two times; when the mass fraction of the molten steel entering the ladle for the first time accounts for 28-40% of the total amount of the molten steel entering the ladle, the hypereutectic high chromium cast iron powder obtained in step ① is preheated at 950-980°C for 120-150 minutes and then added into the ladle, and the mass fraction of the hypereutectic high chromium cast iron powder added accounts for 10-12% of the total amount of the molten steel entering the ladle; after all the hypereutectic high chromium cast iron powder enters the ladle, the remaining molten steel in the electric furnace is discharged into the ladle; ③ When the temperature of the molten steel in the ladle drops to 1506-1521°C, pour it into the crystallizer on the continuous casting machine, and during the continuous casting process, the molten steel in the crystallizer is electromagnetically stirred, the electromagnetic stirring current is 380-400A, and the electromagnetic stirring frequency is 4-5Hz; the continuous casting machine pulling speed is 0.65-0.70m / min; cast into round steel bars with a diameter of φ80-90mm, and the length of the round steel bars is cut into 6-8m; then the round steel bars with a length of 6-8m are placed in a heating furnace for heating, and after the round steel bars are uniformly heated to 1180-1220°C and kept warm for 45-60 minutes, the round steel bars are transported to the continuous cutting machine through a steel bar conveying device with a heat preservation device for cutting to obtain steel sections; then the steel sections are forged into steel balls, and the final forging temperature is controlled at 950-1050°C; ④ When the surface of the steel ball is air-cooled to 825-850°C, the steel ball is sent to a quenching water pool at 28-45°C for quenching; the volume ratio of water to steel ball in the quenching water pool is greater than 10:1; when the surface temperature of the steel ball drops to 90-120°C, it is taken out and immediately placed in a heat treatment furnace at a temperature of 180-210°C for 18-19 hours, and then cooled to a temperature below 135°C; finally, it is taken out of the furnace and air-cooled to room temperature to obtain a ceramic particle reinforced wear-resistant steel ball.
2. The method according to claim 1, It is characterized in that The chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy block are: 6.14-7.88% RE, 3.36-4.21% Mg, 38.62-41.17% Si, ≤1% Ti, ≤1% Al, and the remainder is Fe and unavoidable impurity elements.
3. The method according to claim 1, It is characterized in that The chemical composition and mass fraction of the titanium iron block are: 29.61-30.86% Ti, <8.5% Al, <5.0% Si, and the remainder is Fe and unavoidable impurity elements.
4. A ceramic particle reinforced wear-resistant steel ball prepared according to the method described in any one of claims 1 to 3.
5. Use of the ceramic particle reinforced wear-resistant steel balls prepared by the method according to any one of claims 1 to 3 as grinding balls for mills.
